Immobilization of Rhizopus oryzae Lipase on Zeolit, CaCO3, Silica Gel, and Cow Bone - Maria Bintang; Tri Panji; Susi Saadah (IPB University, 2015)
Food production in Indonesia is constrained by the high cost of lipase that is still imported from abroad. To overcome this problem, research of food production has been conducted using crude extract of lipase produced by indigenous species of fungi Rhizopus oryzae. The R. oryzae is edible indicating that it is safe to be used in the production of food products. Enzymes have an ability to catalyze specific chemical reactions with high efficiency and low energy cost. Enzyme immobilization is a recovery techique that has been studied in several years, using supporting materials as a medium to help enzyme dissolutions to the substrate. Several supporting materials such as zeolit, CaCO3, silica gel, and cow bone were selected by its ability to adsorb lipase. CaCO3 shows enzyme loading rate respectively 99.46%, giving more lipase to adsorb than zeolit (90.69%), cow bone (91.56%), and silica gel (59.63%). In this research, condition factors, such as optimum pH, optimum temperature, and storage ability of the matrix were investigated. Free lipase reacts optimally at pH 7 and temperature 30°C. Identical result showed for lipase in cow bone. Lipase in CaCO3 reacts optimally at pH 8 and temperature 35°C. Lipase in zeolit and silica gel reacts optimally at pH 8 and temperature 30°C. Half life time estimation was one week in storage condition temperature at 4°C and each optimum pH.